Efficiency optimisation based speed control of IPMSM drive. (20th May 2009) - Uddin, M. Nasir; Abera, Fasil
A model based energy optimisation algorithm for speed control of interior permanent magnet synchronous motor (IPMSM) drive is proposed in this paper. The efficiency of variable speed drives can be optimised by either the proper design of the motor or selecting the appropriate control techniques or both. In this work, the efficiency of IPMSM is optimised online based on a developed control technique. The d-axis armature current is utilised to minimise the losses of the IPMSM in a closed loop vector control environment. The completed drive is successfully implemented in real-time using DSP board DS1104 for a laboratory 5 hp motor. It is found from both simulation and experimental results that the efficiency of the proposed IPMSM drive is improved significantly as compared to the conventional id = 0 control technique.